Survey and comparison of operating concept for routing protocols in DTN - Ahmed, Kawakib K.; Omar, Mohd Hasbullah; Hassan, Suhaidi (Science Publications, 2016)
Delay Tolerant Network (DTN) are promising techniques to enable data transmission in challenging scenarios where sophisticated infrastructure is not available and the end-to-end path does not exist at the moment of data transmission.These networks are characterized by a long delay, intermittent connectivity and high error rates.Furthermore, the dynamic topology of the network may change randomly.Therefore, routing is one of the most crucial issues that affect the performance of DTN in terms of data delivery, latency and using resources if node mobility is considered.The routing design in DTN raises many challenges to the networks.Therefore, the problem of how to route a packet from one node to another in DTN is of the essence. This paper puts forward a rigorous survey of various routing protocols as well as performs a comparison of diverse routing strategies regarding significant issues in DTN.